PERSEPSI PEMUDA TENTANG KEBIJAKAN KARTU PRAKERJA DALAM PENANGGULANGAN PENGANGGURAN KOTA SAMARINDA - Fitri Adi; Adam Idris; Fajar Apriani (Jurnal Administrative Reform, 2021)
This study aims to determine the attention of the government in the Samarinda City unemployment reduction, youth perceptions about the pre- work card policy in the City of Samarinda unemployment reduction and the implications of the pre-work card policy in the City of Samarinda unemployment reduction. This type of research used in this study is a combination research method with a concurrent embedded model, data analysis using descriptive statistical method. The results showed that the government has the role of community empowerment and in preparing workforce that is ready to use by providing experience and skills. Youth in Samarinda City are dominantly aware of the pre-work card policy with the main source of information through electronic media. The majority of Samarinda City's youth perceptions stated that they quite agree on the pre- work card policy. Samarinda City's youth perception about the implications of the pre-work card policy states that it is quite capable of dealing with youth unemployment.Keyword: Pre-work Card Policy, Unemployment Reduction, Youth Perception